A decoupled extended power flow analysis based on Newton-Raphson method for islanded microgrids. (May 2020) - Nazari, Amir Ali; Keypour, Reza; Beiranvand, M.H.; Amjady, Nima
Highlights: A decoupled extended power flow method is proposed for islanded microgrids. Partial derivatives of scheduled power injections are included in the Jacobean matrix. The resistive nature of low-voltage microgrids is used to decouple the algorithm. The droop control features of distributed generations are formulated in detail. Different networks are investigated to analyze the performance of the method. Abstract: Recently, microgrid (MG) power flow (PF) studies have gained a lot of attention due to the emergence of autonomous MGs which feature distributed generations (DGs). There are some inherent limitations in the islanded operation mode of MGs which cannot be addressed by conventional PF methods. In this regard, recent studies have proposed some updates to the conventional approaches by inclusion of network frequency as a variable in their modeling and omission of the slack bus from the grid. These considerations specifically in the Newton-Raphson (NR) method change the Jacobean matrix (JM) formulations. This paper concentrates on improving the previous NR methods for MGs which include droop controlled DGs. For this purpose, the partial derivatives of both calculated and scheduled powers are considered in the Taylor series expansion of bus power injections. Thus, the convergence and accuracy of the PF method are enhanced by adding these derivatives in modeling of generations, loads and losses. Moreover, these extended PF equations are decoupled by reformulating the JM based on the consideration that the lines in MGs are mostly resistive, which results in simplified JM calculations and improved convergence speed. The effectiveness of the proposed decoupled extended NR (DENR) method for MG PF analysis is illustrated in several case studies including 6-bus and 38-bus networks. Moreover, two convergence enhancement methods are also incorporated into the proposed approaches and their merits are investigated.